2021
DOI: 10.1186/s13023-020-01661-9
|View full text |Cite
|
Sign up to set email alerts
|

Executive function is inversely correlated with physical function: the cognitive profile of adult Spinal Muscular Atrophy (SMA)

Abstract: Background Spinal muscular atrophy (SMA) issues from mutations in the survival of motor neuron (SMN) 1 gene. Loss or reduction of the SMN protein results in progressive muscle weakness. Whether this protein deficiency also affects cortical function remains unclear. While no data on adult patients exists so far, prior studies in children with SMA indicate cognitive abilities equal or even superior to healthy controls. This may suggest a possible compensatory—neuropsychological and interactional—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
2
16
1
Order By: Relevance
“…However, the WST as a vocabulary test alone is not sufficient to fully assess general intelligence in its entirety; in the future, rather an entire test battery should be used. Surprisingly, the level of functional motor impairment measured by ALSFRS-R showed no association with the cognitive profile of patients, neither in SMA nor in ALS patients, which is in contrast to data by Mix et al (in press) [25]. A likely explanation may be that not the current motor handicap but the level of impairment during childhood and adolescence-the time when the compensational process might have taken place-affects the cognitive profile in a patient's adult life.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the WST as a vocabulary test alone is not sufficient to fully assess general intelligence in its entirety; in the future, rather an entire test battery should be used. Surprisingly, the level of functional motor impairment measured by ALSFRS-R showed no association with the cognitive profile of patients, neither in SMA nor in ALS patients, which is in contrast to data by Mix et al (in press) [25]. A likely explanation may be that not the current motor handicap but the level of impairment during childhood and adolescence-the time when the compensational process might have taken place-affects the cognitive profile in a patient's adult life.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, no difference in the remaining ECAS domains could be seen. Mix et al showed that the cognitive function in SMA is no worse than in healthy subjects (in press) [25]. Therefore, differences in cognitive performance between both groups may not only be explained by ALS-related cognitive impairment but may additionally be attributed to the above-mentioned compensatory developments in childhood in the SMA group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar radiological findings have been described in type I SMA (115). For the most part, neuropsychological studies demonstrate preserved cognition (116)(117)(118)(119). This is with the caveat that these studies are mostly limited to children and omit the more severe clinical phenotypes (120).…”
Section: Spinal Muscular Atrophysupporting
confidence: 71%
“…The only neuropsychological study of adults with type II or type III SMA described normal rather than superior cognitive abilities. This study reported a possible adaptive mechanism of an inverse correlation between executive function and physical ability, but the level of executive function did not exceed healthy controls (116). In contrast, there are indications of attention and executive function deficits in children with type I SMA (120,126).…”
Section: Spinal Muscular Atrophymentioning
confidence: 51%